A Comparative Study of Endoscopic versus Microscopic Cartilage Type I Tympanoplasty - Shakya,Dipesh (2020)
Abstract Introduction The use of endoscope is rapidly increasing in otological and neuro- otological surgery in the last 2 decades. Middle ear surgeries, including tympanoplasty, have increasingly utilized endoscopes as an adjunct to or as a replacement for the operative microscope. Superior visualization and transcanal access to diseases normal- ly managed with a transmastoid approach are touted as advantages with the endoscope. Objectives The present study aimed to compare the outcomes of endoscopic and microscopic cartilage tympanoplasty (Type I) Methods This was a retrospective comparative study of 70 patients (25 males and 45 females) who underwent type I tympanoplasty between March 2015 and April 2016. The subjects were classiﬁed into 2 groups: endoscopic tympanoplasty (ET, n = 35), and microscopic tympanoplasty (MT, n = 35). Tragal cartilage was used as a graft and technique used was cartilage shield tympanoplasty in both groups. Demographic data, perforation size of the tympanic membrane at the preoperative state, operation time, hearing outcome, and graft success rate were evaluated. Results The epidemiological proﬁles, the preoperative hearing status, and the perforation size were similar in both groups. The mean operation time of the MT group (52.63 ± 8.68 minutes) was longer than that of the ET group (48.20 ± 10.37 minutes), but the difference was not statistically signiﬁcant. The graft success rates 12 weeks postoperatively were 91.42% both in the ET and MT groups, that is, 32/35; and these values were not statistically signiﬁcantly different. There was a statistically signiﬁcant improvement in hearing within the groups, both pre- and postoperatively, but there was no difference between the groups. Conclusion Endoscopic tympanoplasty is a minimally invasive surgery with similar graft success rate, comparable hearing outcomes and shorter operative time period as compared to microscopic use.